Pengembangan Desain Produk Berbahan Bambu dengan Menggunakan Strategi Desain di Nagari Kumanis Sijunjung (Studi Kasus ; UKM Kerajinan Bambu di Nagari Kumanis, Kabupaten Sijunjung) - Malik, Kendall; Fernando2, Ferry; Amalia, Silvi (Besaung : Jurnal Seni Desain dan Budaya)
The research focused is on bamboo crafts in Nagari Kumanis, Sijunjung Regency, about the use of bamboo material as a potential product using a design strategy. Bamboo production areas in West Sumatra are mostly produced in Sumpur Kudus district in Nagari Tanjung Bonai Aur and Kumanis, Sijunjung Regency. Nagari has a group called Talago Bamboo Crafts. One of the bamboo handicraft centers that has long been developing in West Sumatra is the Tanjung Bonai Aur and Kumanis bamboo crafts. It is known that bamboo crafts in Kumanis nagari are quite unique in terms of technical aspects, but in the aspect of design strategies and market strategies of bamboo products have not been explored properly. So that the economic and production cycle moves in place. Bamboo plantations in West Sumatra belong to communities that are managed independently by the population. Bamboo in the Kumanis nagari community is important by the economic wheel and their economic bamboo efforts as a side job. In fact, Minang residents already have a bamboo garden that is indirectly as a bamboo farmer. This is an opportunity for writers in this design project to provide ideas and design ideas to communities and small industries (homeindustry). In fact, bamboo material has not been specially processed for product design, especially for bamboo product design and Design Strategies. the problem of this research is how to improve, process and utilize bamboo material as one of the development of interior complementary designs and in accordance with market needs and tastes.